Global Issues of Citizenship and The Development of Civic Education for University Students in Indonesia - *, Rusnaini (Sebelas Maret University, 2016)
Some preliminary observations on the students of civic education at Universitas Sebelas Maret (UNS) in Indonesia indicated that they were not able to map various local and global problems. They were not capable of questioning the policies of their government on the related issues as well. This study argues that the studentsâ incapability stems from the components of the civic education for university students which have not sufficiently covered various issues related to the interconnectedness of national and global issues. In fact, along with global changes in the last few decades, the Indonesian civic education should have given greater attention to global issues as one of its core components. In this way, it can facilitate some reflections and dialogues on global changes that we have been facing, such as 1) climate change, 2) global of justice and social harmony, 3) human right issues as security, 4) global peace and global governance, and 5) dialogues among civilizations. This study attempts to develop an effective civic education that adequately incorporates global issues for Indonesian university students. It carefully considers some perspectives on citizenship issues, particularly from Beck (1997) on risk society and Linklater (2002) on cosmopolitan citizenship. It applies the Research and Development (R & D) methodology of Borg and Gall (1983) by taking UNS students as a case study. The duration of the study will be two years, encompassing the following steps in the R & D cycle (1) research, analysis and needs assessment; (2) data collection; (3) model development; (4) validation of the model; (5) revision of the model; (6) preliminary testing of the model; (7) wider revision of the model; (8) main field testing; (9) final model revision. It is through this R & D cycle that a meaningful model of civic education that students, being the consumers of the product, value most can be better developed.